Factors influenced on heat gains and heat losses in buildings - Lis, A. (Видавництво Національного університету «Львівська політехніка», 2007)
The paper presents the results of investigations on building’s heat gains and heat losses. The heat balance conditions in selected buildings were observed. The factors, which influence heat gains and heat losses in analysed building were identified. The changes of value of these quantities on the influence of individual factors were estimated.